Hubungan Tingkat Pengetahuan, Dukungan Keluarga, dan Peran Petugas Kesehatan Terhadap Kepatuhan Minum Obat pada Lansia Penderita Hipertensi di Puskesmas Kintamani V - Ni Luh Sasih; I Gusti Ayu Agung Septiari; Ni Putu Wintariani; I Putu Riska Ardinata (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Hypertension or better known as high blood pressure is often experienced by the elderly where blood pressure is above the normal limit of 120/80 mmHg. Adherence to taking medication in the elderly is very important because regular use of blood pressure medication can keep blood pressure under control and controlled. This study will be carried out at Kintamani V Health Center, because it is the highest hypertension sufferer after Bangli Health Center. This study aims to examine the relationship between the level of knowledge, family support, and the role of health workers on medication adherence in elderly people with hypertension at Kintamani V Health Center. The research method used is a type of quantitative research using a cross-sectional design. Data were collected using questionnaires. The results showed that the majority of respondents had a high level of knowledge (68.3%), as 51.7% of respondents received good family support, and the majority of respondents had the role of health workers as many as 73.3% of respondents. Statistical analysis showed that there was a significant relationship between the level of knowledge (p-value = 0.000), family support (p-value = 0.000) and the role of health workers (p-value = 0.000) with medication adherence in elderly people with hypertension. In conclusion, this study shows that there is a significant relationship between the level of knowledge, family support, and the role of health workers on medication adherence in elderly people with hypertension at Kintamani V Health Center.